The Definitive Guide to SQLite - Owens, Mike (Apress : Imprint: Apress, 2006)
Traditional relational databases and embedded databases both have shortcomings that can leave a developer perplexed. So for many people, the solution resides in an open source embeddable database with an amazingly small footprint (less than 250 kilobytes). SQLite packs a powerful array of features and can handle databases as large as 2 terabytes. It offers a flexible set of datatypes and the ability to perform transactions, and it is supported by languages like C, PHP, Perl, and Python. And because SQLite's databases are completely file based, privileges are granted at the operating system level, allowing for easy and fast user management. The Definitive Guide to SQLite is the first book to devote complete coverage to this powerful database. It offers you a thorough overview of SQLite capabilities and APIs, while remaining cognizant of newcomers who may be making their first foray into a database environment with SQLite. This book serves as both a first-time tutorial and future reference guide.